Comparing river basins world-wide and contrasting inland fisheries in Africa and Central Amazonia - Petrere, M. [UNESP]; Welcomme, R. L.; Payne, A. I. (Wiley, 1998)
An analysis of covariance relating basin area (A, km2) to river length (L, km) and discharge rate (D, m3 s-1) was performed for two continents and showed that the two covariates (L and D) were highly significant and that the strength of the relationship changed between continents. For comparison, D was excluded but the result remained the same. Although geomorphological models are useful for establishing global levels of production, these regressions should be applied with caution. Historically, simple statistical models were developed to predict fish catches in rivers. These, based upon regression of catches on channel length or basin area for Africa and Central Amazonia, are contrasted in this paper because of their generally similar approach.
Keywords: Africa; Amazon; Fluvial geomorphology; Tropical river fisheries; catch prediction; inland fishery; modelling; South America, Amazonia